In vitro skin penetration of clobetasol from lipid nanoparticles: drug extraction and quantitation in different skin layers - Luís Antônio Dantas Silva; Stephânia Fleury Taveira; Eliana Martins Lima; Ricardo Neves Marreto (Universidade de São Paulo, 2012)
Clobetasol propionate (CP) is a potent topical corticosteroid that causes several cutaneous and systemic side effects. In the present work, CP was encapsulated in nanostructured lipid carriers (NLCs) to increase drug retention in the outer skin layers and improve the safety of topical therapy. NLCs were prepared using a microemulsion technique with a mixture of lecithin, taurodeoxycholate, stearic acid, and oleic acid. In vitro penetration studies were performed in a modified Franz-type diffusion cell, and porcine ears were used as a model of human skin. A simple and sensitive liquid chromatographic method was developed and validated for clobetasol determination in different skin layers. NLCs presented uniform size distribution, high zeta potentialand entrapment efficiency values (> 98%). The analytical procedure was validated according to FDA guidelines. Clobetasol recoveries from skin samples were higher than 85%, with no interference of skin components and NLC ingredients. In experiments, after 6 h, a higher drug accumulation in the stratum corneum arising from NLCs compared to aqueous CP solution was observed. Thus, the NLCs demonstrated high potential for targeting CP to the skin and ensuring drug accumulation in the stratum corneum. Proprionato de clobetasol (CP) é um potente corticóide tópico, que apresenta vários efeitos adversos cutâneos e sistêmicos. No presente trabalho, CP foi encapsulado em carreadores lipídicos nanoestruturados (NLCs) visando aumentar a retenção do fármaco nas camadas superficiais da pele e a segurança da terapia tópica. NLCs foram preparados usando a técnica de diluição de microemulsão com mistura de lecitina, taurodesoxicolato, ácido esteárico e ácido oléico. Estudos de penetração in vitro foram realizados em células de difusão de Franz modificadas usando pele de orelha de porco como modelo de pele humana. Um método simples e sensível de cromatografia líquida foi desenvolvido e validado para a determinação de clobetasol nas diferentes camadas da pele. NLCs apresentaram distribuição de tamanho uniforme e valores elevados de potencial zeta e eficiência de encapsulação (>98%). O procedimento analítico foi validado de acordo com as diretrizes do FDA. A recuperação de clobetasol a partir das amostras de pele foi maior que 85%, sem interferência dos componentes da pele e dos excipientes das NLCs. Após 6 horas de experimento observou-se maior acúmulo do fármaco a partir das NLCs comparado à solução aquosa de CP. Dessa forma, as NLCs mostraram elevado potencial para direcionar o CP para a pele, pois elas possibilitaram o acúmulo do fármaco no estrato córneo.